LITERATURE REVIEW: HUMAN FACTORS AND ERGONOMICS (HFE) IN THE FOOD INDUSTRY - Dewantari, Nustin Merdiana; Herlina, Lely (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2022)
In the era of sustainable development, humans are a system because of their role in development. The food industry is growing fast at this time, and it is important for the sustainability of a country, while the human factor and ergonomics will provide benefits if applied. Therefore, it is necessary to conduct a literature study. This study aims to provide a better understanding and research opportunities on human factors and ergonomics in the food industry. This review literature search was carried out using Publish and Perish based on the Google Scholar database with the search year 2015-2022, then checking the journals one by one. There were twenty-seven articles discussing human factors and ergonomics in the food industry. Based on the year of research, research on human factors and ergonomics began in 2017 and has increased every year until 2019. RULA, SNQ, and REBA are the ergonomics data analysis techniques most widely used by researchers, and Elsevier became the publisher most used. The focus of the research area is large on improving ergonomics. The discussion of human factors and ergonomics can be implemented in various sectors, including the food industry, the integration of human factors with other fields is also worth considering.